Predictive value of clinical indices in detecting aspiration in patients with neurological disorders. Issue 4 (1st October 1997) - Mari, Fabiola; Matei, Monica; Ceravolo, Maria Gabriella; Pisani, Anna; Montesi, Alfeo; Provinciali, Leandro
Abstract : OBJECTIVES: (1) To evaluate the predictive value of a detailed clinical screening of aspiration in patients withneurological diseases, both with and without symptoms of dysphagia taking videofluoroscopy as the gold standard; (2) to assess the existence of risk factors for silent aspiration, measuring the cost-benefit ratio of radiological examination. METHODS: 93 consecutive patients meeting the diagnostic criteria for a neurological disease with a risk of swallowing dysfunctions (cerebrovascular accidents, brain injury, Parkinson's disease, multiple sclerosis, amyotrophic lateral sclerosis, myotonic dystrophy, and abiotrophic diseases) underwent a detailed clinical assessment using a 25 item form to check for symptoms of dysphagia and impairment of the oropharyngeal swallowing mechanism. The 3 oz water swallow test was also performed to assess the aspiration risk. Sensitivity, specificity, positive predictive, and negative predictive values (NPV) of dysphagia, history of cough on swallowing, and 3 oz test positivity, versus videofluoroscopy documented aspiration, taken as the gold standard, were measured in all the patients and in subgroups with different neurological disorders. RESULTS: Non-specific complaints of dysphagia showed a very poor predictive value, whereas the symptom "cough on swallowing" proved to be the most reliable in predicting the risk of aspiration, with 74% sensitivity and specificity, 71% positive predictive, and 77% negative predictive value. The standardised 3-oz test had a higher predictive potential than the clinical signs, but had low sensitivity. The association of cough on swallowing with the 3 oz test gave a positive predictive of 84%, and an negative predictive value of 78%. In cases where the clinical tests failed to detect any impairment, videofluoroscopy documented only a low risk (20%) for mild aspiration. CONCLUSIONS: The association of two clinical items (such as history of cough on swallowing and 3 oz test positivity) provides a useful screening tool, the cost:benefit ratio of which seems very competitive in comparison with videofluoroscopy in aspiration risk evaluation.